Socio-Psychological and Design Features Related to Transport Choices: A Focus Group Research in the Metropolitan Area of Cagliari (Sardinia, Italy) - Manca, Sara; Tirotto, Francesca Ausilia; Mura, Nicola; Fornara, Ferdinando (Frontiers in Psychology, 2022)
Due to the environmental and health impact of the private transport sector, social scientists have largely focused on psychosocial and contextual factors associated with people’s choice of transport means. The present research aimed to contribute to this line of research by applying a user-centered approach with the aim to take into account the specific environmental and social context of the metropolitan area of Cagliari city (Sardinia, Italy). To accomplish this aim, four groups of people were matched according to their shared starting point, that is car users vs. public transport users (Study 1), and light-rail users vs. non-light-rail users (Study 2). Groups were interviewed using the focus group method. Participants were invited to discuss their everyday travel experiences and to exchange their ideas on different sustainable (e.g., bicycles and public transport) and less sustainable (i.e., private cars) means of transport. Both consolidated drivers/barriers in the field of environmental psychology (e.g., perceived behavioral control, social norms) and public transportation design features (e.g., lighting) have been investigated. Other than highlighting the importance of socio-psychological factors to promote more sustainable transport choices as in previous studies, the present research offers an insight into how these aspects and factors are shaped and experienced in the narratives of residents.